Kepuasan Pasien BPJS: Tinjauan Terhadap Kualitas Pelayanan, Kelompok Acuan, dan CRM - Dewi Sekar Arum; Didit Darmawan; Rafadi Khan Khayru; Fayola Issalillah; Yeni Vitrianingsih (PPIMAN Pusat Publikasi Ilmu Manajemen, 2023)
This study aims to analyse the impact of service quality, reference group, and customer relationship management on BPJS Kesehatan patient satisfaction using purposive sampling method on 100 BPJS Kesehatan user respondents. The research findings show that service quality, reference group, and customer relationship management have a positive and significant influence on BPJS Kesehatan patient satisfaction. These results underscore the importance of these aspects in increasing patient satisfaction levels, reflecting their positive experiences with BPJS health services. This study provides insight into the importance of service quality, the role of reference groups, and the implementation of customer relationship management in improving the satisfaction of patients using BPJS Kesehatan.